Modelling Cultural Dynamics: A Macroscopic Approach To Cultural Transmission In The Prehistoric Aegean - Evans,TS; Hunt,E; Knappett,C; Rivers,RJ (2007)
In this paper we pursue a novel transdisciplinary approach to the question of cultural dynamics, focussing particularly on the transmission of cultural traits across socio-physical space. In order to think through some of the themes involved we take as a case study an inter-regional phenomenon known as Minoanisation (Wiener 1990; Broodbank 2004). This term describes a set of processes observed in the prehistoric Aegean (specifically the Middle and early Late Bronze Age) whereby Minoan cultural traits find themselves transmitted beyond the Minoan sphere, i.e. the island of Crete. That is to say, communities in regions such as the Cyclades, the Dodecanese, coastal Asia Minor and the Greek mainland adopt aspects of Cretan culture, both in the form of actual imports from Crete and also local imitations thereof. These cultural elements include pottery shapes and styles, stone vases, loomweights and wall paintings; not only new forms of material culture, but also, presumably, new cultural practices.